Experiences of Filipino Nurses on Salary Incentive City of San Fernando La Union, Philippines - Titus, Auta Tanko (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Research has shown that there is large scale migration of Filipino nurses in health industry to other countries for greener pasture, and this trend is a threat to nation building especially in developing country like Philippines. Understanding variables that influence such movement is very important in light of the global human resource crisis; hence policy implementation of financial incentives is important to guide policy makers, as these are the most commonly used staff retention strategies. Qualitative research utilizing Husserl (descriptive) and Heidegger (interpretive) hermeneutics research design was employed to explore Experiences of Filipino Nurses on Salary Incentive. 14 participants were interviewed using snowball sampling technique, focusing on years of experience and awareness on provisions of laws on salary incentives. Content analysis was utilized to group the answers of the participants to the questions asked in the structured interview guide. Analysis of the gather data indicates that some nurses are unaware of the existing laws on salary incentives; Nurses are experiencing overwork especially those in private hospitals (12hours in a shift with low salary) with low pay; Nurses both private and public hospitals are not enjoying implementation the salary incentives laws; and social support activities is none existence in all the hospitals under study. Conclusively, working experience is a prerequisite while abundant qualified license nurses have no employment opportunity. Based on the findings, the study recommended measures to relevant authority for consideration and possible adoption, and parallel study maybe conducted in the region/other regions on salary incentive. Keywords: Nursing Services, Salary Incentive